Implementation Of Child Protection Laws - Khozinatul Asrori; Imam Sukardi (Risâlah Jurnal Pendidikan dan Studi Islam, 2024)
In Indonesia, child protection is contained in Article 28b No. 2 of the 1945 Constitution. In addition, it is also contained in Law no. 3 of 2014 concerning Amendments to Law no. 23 of 2002 concerning Child Protection that there are four special areas that need to be considered in the implementation of child protection, namely: the fields of Religion, Education, Health and socio-culture. The five main pillars (parents, family, community, government and state) have a close relationship in carrying out child protection tasks in forms and efforts that are appropriate to the level of ability in various forms of business carried out and under certain conditions. As the Nahdlatul Community Organization has several programs that support efforts to protect children. In this research study, researchers used qualitative research which describes and describes some of the existing findings, especially in this study related to the application of the Child Protection Act in the NU Community Organization of Pagerwojo Perak Jombang Branch. This research shows that the implementation of the Child Protection Act at the NU Branch Pagerwojo Perak Jombang Community Organization has been implemented and so far it has only played a role in efforts that are preventive in nature or only prevention of child protection cases in the form of socialization roles carried out in various programs that have been proclaimed.